A self-determination theory based investigation of life skills development in youth sport. Issue 8 (18th April 2022) - Cronin, Lorcan; Ellison, Paul; Allen, Justine; Huntley, Emma; Johnson, Laura; Kosteli, Maria Christina; Hollis, Anna; Marchant, David
ABSTRACT: This study investigated if basic need satisfaction and frustration mediated the associations between autonomy-supportive and controlling coaching behaviours and participants' development of eight different life skills in youth sport. British sports participants ( N = 309, M age = 14.71) completed measures assessing the study variables. Correlational analyses showed that autonomy-supportive coaching behaviours were positively associated with the satisfaction of participants' three basic needs (autonomy, competence, and relatedness) and their development of all eight life skills, whereas controlling coaching behaviours were only positively related to the frustration of participants' three basic needs. Mediational analyses revealed that satisfaction of all three basic needs combined (total need satisfaction) mediated the associations between autonomy-supportive coaching behaviours and participants' development of the eight life skills. Relatedness satisfaction mediated the associations between autonomy-supportive coaching behaviours and participants' development of all eight life skills except for goal setting; autonomy satisfaction mediated the associations between autonomy-supportive coaching behaviours and participants' time management skills; and competence satisfaction mediated the associations between autonomy-supportive coaching behaviours and participants' goal setting and emotional skills. Based on such findings, coaches should look to display autonomy-supportive behaviours that help to satisfy participants' three basic psychological needs and promote their life skills development in sport.